A Preliminary Review of Multiscale Fret as Innovation of Ergonomic Guitar - Sulistiono, Sulistiono; Suhardi, Bambang; Ishartomo, F; Nugraha, I (UUM Press, 2021)
The development of multiscale fret as innovation of ergonomic guitar concept aims to make this innovation applied more by guitar luthiers in designing a guitar signature that is modern and ergonomic. This concept has its own advantages, not only producing specific and organic tones, but also has benefits that can minimize the risk of repetitive strain injuries that are often experienced by guitar players. Therefore, multiscale fret has begun to be widely developed and has become one of the alternative innovations that can be applied by guitar luthiers that still adopt conventional fret concept. This paper conducts an preliminary information of the innovation of multiscale fret in a guitar that is associated with aspects of ergonomic comfort. In further research, this is expected to be a reference to understand the basic of multiscale fret and a stepping stone in conducting more systematic review regarding the effectiveness of the performance of human-centered musical instruments.